The Philosopher's Stone for Sustainability Proceedings of the 4th CIRP International Conference on Industrial Product-Service Systems, Tokyo, Japan, November 8th - 9th, 2012 - Shimomura, Yoshiki; Kimita, Koji.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Industrial Product-Service Systems (IPS2), which is defined as an integrated industrial product and service offering that delivers value in use, has expanded rapidly over the last decade. IPS2 has allowed us to achieve both high added value and high productivity and has enriched our QOL by improving the performance of products and services. We are now struggling with many awkward issues related to sustainability, but IPS2 is expected to be the philosopher s stone for solving these issues. Following the pattern of conferences held in Cranfield in 2009, Linköping in 2010, and Braunschweig in 2011, the fourth International CIRP Conference on Industrial Product-Service Systems, held on November 8-9, 2012, in Tokyo, will cover various aspects of IPS2. Topics planned for this year s conference reflect the latest IPS2 information in both the natural sciences and humanities and include case studies from various industries. IPS2 is still a relatively new field, so it is important to keep track of the entire context in order to promote more cross-sectional cooperation between multimodal fields and disciplines. The fourth International CIRP Conference on Industrial Product-Service Systems will serve as a vital platform for such collaborations and the discussion of new scientific ideas.
Special Keynote Presentation -- Keynote Presentations -- PSS Design and Development -- Uncertainty in Networks for PSS -- Service Engineering and Service Science -- PSS-Business Models -- Organizational Issue and Management -- Planning for PSS Implementation -- Customer Analysis -- PSS and Process Modeling -- Lifecycle Management and Sustainability -- From Academic Disclipline to Industrial Applications -- Planning for PSS Implementation -- PSS and ICT -- Future PSS Research Forum -- Strategy, Marketing and Economics.
Keywords: Engineering; Engineering design; Engineering economy; Engineering; Engineering Economics, Organization, Logistics, Marketing; Engineering Design; Production/Logistics/Supply Chain Management